2016
DOI: 10.1002/ams2.195
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is a predictive factor for prolonged intensive care unit stays in high‐energy blunt trauma patients

Abstract: Aim Sarcopenia has been increasingly reported as a prognostic factor for outcome in settings such as cirrhosis, liver transplantation, and emergent surgery. We aimed to elucidate the significance of sarcopenia in severe blunt trauma patients. Methods We retrospectively analyzed 84 patients emergently admitted to the intensive care unit at Kyushu University Hospital (Fukuoka, Japan) from May 2012 to April 2015. We assessed the amount of skeletal muscle present according to computed tomography and its relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 15 publications
1
67
0
Order By: Relevance
“…A more holistic approach was taken by Leeper et al , normalizing psoas CSA using a calculated value for body surface area (BSA) 6. Akahoshi et al similarly used calculated BSA to generate an estimate for psoas CSA, and defined sarcopenia as a difference between estimate and actual psoas CSA 22…”
Section: Discussionmentioning
confidence: 99%
“…A more holistic approach was taken by Leeper et al , normalizing psoas CSA using a calculated value for body surface area (BSA) 6. Akahoshi et al similarly used calculated BSA to generate an estimate for psoas CSA, and defined sarcopenia as a difference between estimate and actual psoas CSA 22…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, the association between sarcopenia and postoperative morbidity has seen a progressively growing interest with an emerging body of literature showing a remarkable relationship between sarcopenia and poor surgical outcomes across multiple specialties. [9][10][11] In a study by Levolger et al, overall survival of hepatobiliary cancer patients with low skeletal muscle mass was significantly lower than their counterparts. 25 Similarly, studies by Suzuki et al and Tsukioka et al demonstrated that patients with early-stage non-small-cell lung cancer amenable to surgery who had low skeletal muscle mass were at greater risk of short-term and long-term adverse events postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were also found to require longer periods of mechanical ventilation and had longer ICU stays. 10 Prolonged hospital stays have been linked to low-skeletal muscle mass, which in turn has been associated with increased health-care costs. In fact, results from a recent, large systematic review of 452 patients receiving alimentary tract oncologic surgery showed that sarcopenic patients had longer hospital stays with a subsequently higher health care cost burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT images, which are feasible in the emergency setting and completely objective, are usually carried out preoperatively for all patients with perforation panperitonitis. Because adjustment of skeletal muscle volume using body weight and body surface area is difficult in the emergency setting, we judged that using body height only was appropriate in the present study.…”
Section: Discussionmentioning
confidence: 99%